2020
DOI: 10.1021/acsami.0c09364
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Enabled Antimicrobial Nanocapsules for Selective Elimination of Staphylococcus aureus

Abstract: Targeted bactericide nanosystems hold significant promise to improve the efficacy of existing antimicrobials for treatment of severe bacterial infections, minimizing the side effects and lowering the risk of the development of antibiotic resistance. In this work, we developed antibody-functionalized nanocapsules (NCs) containing antibacterial essential oil (EO) for selective and effective eradication of Staphylococcus aureus . Antibacterial EO NCs were produced via self-assembly nanoenca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The use of low-density particles such as liposomes or nanomaterials as substrates for the LbL deposition of PE can be difficult since centrifugation or sedimentation can’t be used for the separation of the multilayered materials from the deposition solution [ 8 ]. The most important biomedical applications of the multilayers are the incorporation and release of active substances (drugs, enzymes, proteins, liposomes) [ 116 , 117 ], tissue engineering [ 118 , 119 ], the fabrication of films with antimicrobial properties [ 120 , 121 , 122 ], and biosensing [ 123 , 124 ]. Figure 5 highlights the main biomedical applications of PEMs, which are briefly described in this section.…”
Section: Biomedical and Environmental Applications Of Polyelectrolyte Multilayersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of low-density particles such as liposomes or nanomaterials as substrates for the LbL deposition of PE can be difficult since centrifugation or sedimentation can’t be used for the separation of the multilayered materials from the deposition solution [ 8 ]. The most important biomedical applications of the multilayers are the incorporation and release of active substances (drugs, enzymes, proteins, liposomes) [ 116 , 117 ], tissue engineering [ 118 , 119 ], the fabrication of films with antimicrobial properties [ 120 , 121 , 122 ], and biosensing [ 123 , 124 ]. Figure 5 highlights the main biomedical applications of PEMs, which are briefly described in this section.…”
Section: Biomedical and Environmental Applications Of Polyelectrolyte Multilayersmentioning
confidence: 99%
“…The antimicrobial activity of the obtained multilayer was tested on two bacterial strains, Streptococcus aureus and Escherichia coli , demonstrating not only inhibitory activity on the tested bacterial strains but also a controlled-release of the antibiotic, which appeared as a result of the acidification of the environment under the action of secondary metabolites released by the microorganisms (lactic acid, acetic acid). Ivanova et al [ 120 ] reported the construction of antimicrobial composite materials based on the LbL assembly of HA and aminocellulose (AC) on monobutyl ester of poly (methylvinyl ether/maleic) acid template. The antibiofilm formation activity of the multilayered particles obtained was assessed, demonstrating 94% reduction of Escherichia coli and 40% reduction of Streptococcus aureus development.…”
Section: Biomedical and Environmental Applications Of Polyelectrolyte Multilayersmentioning
confidence: 99%
“…Furthermore, Ivanova et al developed antibody-functionalized self-assembled nanocapsules comprising zein plant protein and containing oregano essential oils. This approach allows for the specific targeting of S. aureus bacterial strains while reducing the dosage and the system’s toxicity [ 125 ]. Other bioactive compounds that can be used as antimicrobial agents include antimicrobial glycolipids, such as sophorolipids and rhamnolipids encapsulated into chitosan nanoparticles [ 126 ], and antimicrobial peptides, such as the SET-M33 peptide, encapsulated into dextran nanoparticles [ 127 ].…”
Section: Antimicrobial Applications Of Polymeric Nanoparticlesmentioning
confidence: 99%
“…The functionalized catheters were placed in contact with the previously cultured cells and the viable cells were quantified using AlamarBlue assay kit (Ala-marBlue®, Invitrogen) after 24 h and 7 days of contact [24]. The cells' morphology was also observed by Live/Dead® Viability/Cytotoxicity assay kit for mammalian cells after exposure of the cells to the coated catheters for 24 h and 7 days as previously described [25]. (n = 9), 4-5 months of age and mean body weight of 3 kg, were divided into 3 groups as follow: 1st groupis the control group of noncatheterized animals; 2nd groupis the group of animals catheterized with pristine silicone Foley catheters (size 8 French) for 7 days and the 3rd groupis composed of rabbits catheterized with hybrid ZnO@AM NPs-coated catheters for 7 days.…”
Section: Cytotoxicitymentioning
confidence: 99%